Effect of Water Deficit and Burial Depth on The Germination of Periploca angustifolia - Dghim Fairouz; Boukhris Makki; Neffati Mohamed; Chaieb Mohamed (Ekológia (Bratislava), 2024)
Periploca angustifolia (Labill.) is a multipurpose xerophytic shrub in the Apocynaceae, which is widely disturbed in arid zones. This shrub is often used in programs for the rehabilitation of degraded areas, so it is essential to investigate the impact of environmental factors (drought, burial depth) on seed germination patterns. During 20 days, germination responses of seeds were determined over a wide range of constant temperatures (25 °C), polyethylene glycol PEG-6000 solutions of different osmotic potentials (0 to -1.6 MPa), and burial depths (1–8 cm). The highest germination percentages (99%) were obtained under control conditions without PEG, and increasing osmotic pressure progressively inhibited seed germination, which was about 2% at -1.6 MPa. When seeds were buried deep, there was a significant decrease in seedling emergence percentage and rate. Seedlings of P. angustifolia emerged well at depths of 1–2 cm with the highest emergence percentage of 74 and 69%, respectively. They could not emerge when the sand burial depth was higher than 4 cm.